A new species of Phylloicus Müller 1880 (Trichoptera: Calamoceratidae) from Espírito Santo State, southeastern Brazil - Barcelos-Silva, Patrik; Desidério, Gleison Robson; Pes, Ana Maria (Zootaxa, 2017)
The worldwide caddisfly family Calamoceratidae comprises about 175 extant species in eight genera (Holzenthal et al. 2007). Among these, two are exclusively recorded from the Neotropics: Banyallarga Navás with 18 described species (Prather 2004) and Phylloicus Müller with 57 described species (Prather 2003, Dumas & Nessimian 2010, Santos & Nessimian 2010, Quinteiro et al. 2011), both genera recently reviewed by Prather (2003, 2004).